Management of Student Independence Development in Pesantren - M Sirojut Tholibin (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2022)
This research is a field research with a qualitative approach. Data collection techniques using observation, documentation and interviews. Data analysis using induction and deduction models. After the data is grouped by type, the researcher re-checks the data, so that the data has no errors and can be presented in writing in the form of a research report. The results showed that the management of developing the independence of students at the Daruttauhid Al-Alawi Islamic Boarding School was carried out in three stages, namely (1) Planning was in place before the independence program was implemented such as holding meetings, selecting independence programs, and others. The planning stage includes: curriculum planning, teaching materials, personnel, facilities and infrastructure, and program planning; (2) The implementation of the program is carried out in several stages including carrying out teaching and learning activities, organization, routine compulsory Islamic boarding school activities, daily student activities, supporting activities, and boarding school discipline rules; (3) Supervision and evaluation of the program, caregivers and administrators as well as the community participate in evaluating these activities. If there are weaknesses, then input will be given for improvements in the future.